2010
DOI: 10.1021/nn1005182
|View full text |Cite
|
Sign up to set email alerts
|

Brightly Luminescent Organically Capped Silicon Nanocrystals Fabricated at Room Temperature and Atmospheric Pressure

Abstract: Silicon nanocrystals are an extensively studied light-emitting material due to their inherent biocompatibility and compatibility with silicon-based technology. Although they might seem to fall behind their rival, namely, direct band gap based semiconductor nanocrystals, when it comes to the emission of light, room for improvement still lies in the exploitation of various surface passivations. In this paper, we report on an original way, taking place at room temperature and ambient pressure, to replace the sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
103
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(116 citation statements)
references
References 52 publications
(100 reference statements)
12
103
0
1
Order By: Relevance
“…At RT, the relaxation rate amounts to ,10 11 s 21 , which translates into the relaxation "decay time" of ,10 ps. This is a very fast process compared with the photoluminescence (PL) decay time in the SiNCs under study 5,24 (2 ns), which implies that the high-energy wing should not be observed. However, as a result of the strong size dependence, the relaxation time can change by several orders of magnitude with only a 10% change in size and can reach values as high as nanoseconds 32,33 .…”
Section: Trionic Structurementioning
confidence: 94%
See 3 more Smart Citations
“…At RT, the relaxation rate amounts to ,10 11 s 21 , which translates into the relaxation "decay time" of ,10 ps. This is a very fast process compared with the photoluminescence (PL) decay time in the SiNCs under study 5,24 (2 ns), which implies that the high-energy wing should not be observed. However, as a result of the strong size dependence, the relaxation time can change by several orders of magnitude with only a 10% change in size and can reach values as high as nanoseconds 32,33 .…”
Section: Trionic Structurementioning
confidence: 94%
“…Details of the preparation procedure and the investigation of the direct-bandgap switch-over in this material were published elsewhere 5,24,29 . The strain-engineered direct-bandgap SiNCs under study are characterized by short radiative lifetime 5,24 of 10 ns and a mean SiNC diameter of 2.523 nm 24,30 . Room-temperature single-NC spectroscopy of the oxidized precursor was also performed, but no signs of spectral structure appeared 20 (see also Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While crystalline Si (c‐Si) QDs have been extensively studied within the last decade,14, 15, 16, 17, 18, 19 investigation of amorphous Si (a‐Si) QDs properties has been very limited. One of the reasons for this limited effort is represented by the synthesis difficulties: during synthesis, it is challenging to preserve both the individuality of the QDs and their amorphous nature as QDs tend to aggregate with consequent loss of the quantum‐confined state.…”
mentioning
confidence: 99%